Comparison of global dementia discussions: perspective from the world young leaders in dementia. (12th December 2016) - Booi, Laura; Newman, Kristine; Jackson, Piper
Abstract : Purpose: The purpose of this paper is to critically reflect on the global dementia prevention views of the Japanese leaders at both the Japanese Young Leaders in Dementia Event and the Japanese Global Legacy Against Dementia event, from a Canadian perspective. Design/methodology/approach: This paper undertook a global comparison of the discussion and recommendations from both the Japanese Young Leader Event and the satellite Global Dementia Legacy Event. Findings: The paper provides insights about the cultural and intergenerational differences in both the Japanese solutions compared to the Canadian solutions. Originality/value: The authors encourage leaders involved in global prevention dementia discussions to remember the importance of context, in regards to both cultural and intergenerational collaborations, in the search for global dementia solutions.